2017
DOI: 10.1615/critreveukaryotgeneexpr.2017019532
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins in Brain Aging and Neurological Disorders

Abstract: The many ways of aging have been and continue to be investigated. For this reason, over many years, several studies have resolved some of the genetic details underlying aging processes. It resulted in the identification of a yeast gene known as Sir2, which is a longevity modulator. Sir2 and SIRT1 are the mammalian homologs of yeast genes. Sirtuins (including SIRT1) play an important role in aging of the brain and the metabolic regulation pathway in mammals. Aging in the brain is caused by the loss of neurophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…The well-known evolutionary conserved enzymes, that act as deacetylases and ribosyltransferases, are represented by Sirtuins. Based on the different intracellular localizations it is possible distinguish in mammalian 7 sirtuins, which participate to several cell functions such as DNA damage repair, cell cycle, metabolic response to nutrient availability and protection from neurological degeneration [ 189 , 190 , 191 ]. SIRT1 is predominantly nuclear protein but it has been demonstrated that it is able to translocate rapidly from nucleus to cytoplasm, depending on the cellular type and energy status of cell [ 190 ].…”
Section: Genetic Impact On Agingmentioning
confidence: 99%
“…The well-known evolutionary conserved enzymes, that act as deacetylases and ribosyltransferases, are represented by Sirtuins. Based on the different intracellular localizations it is possible distinguish in mammalian 7 sirtuins, which participate to several cell functions such as DNA damage repair, cell cycle, metabolic response to nutrient availability and protection from neurological degeneration [ 189 , 190 , 191 ]. SIRT1 is predominantly nuclear protein but it has been demonstrated that it is able to translocate rapidly from nucleus to cytoplasm, depending on the cellular type and energy status of cell [ 190 ].…”
Section: Genetic Impact On Agingmentioning
confidence: 99%
“…SIRT1 has a variety of physiological effects in many diseases, including cancer, metabolic diseases, and degenerative diseases (Haigis & Sinclair, 2010). It is abundant in brain tissue, and its role in the central nervous system has been extensively studied (Qadir & Anwar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Silent mating type information regulation 2 homolog 1 (SIRT1) is an NAD + -dependent deacetylase (Cohen et al, 2004; Bordone and Guarente, 2005). In the brain, SIRT1 is mainly expressed in neurons and has numerous biological functions, including regulation differentiation, metabolism, cell survival, and aging (Qadir and Anwar, 2017). It has been reported that SIRT1 activation attenuates hyperglycemia and plays an important mediatory role in treating diabetic complication (Li X. N. et al, 2017; Zhang Q. et al, 2018; Zhang Y. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%